Evidence of validity and reliability of the environmental action scale in Peruvian university students - Serpa-Barrientos, Antonio; Pérez-Flores, Enrique Giovanni; Bellido-Figueroa, Gerardo Manuel; Saintila, Jacksaint (Frontiers in Psychology, 2023)
Background: The environmental action scale is used to measure the degree of participation in collective environmental actions and has been shown to have adequate psychometric properties in developed countries. However, there are still no studies that have evaluated its performance in the Peruvian population. Methods: In this instrumental study, the environmental action scale (EAS) was translated, adapted, and validated. The EAS was administered to 352 university students between 18 and 35 years of age (Mage = 23.37, SD = 2.57) from different cities in Peru. A validity analysis was performed using two sources of evidence: content validity and internal structure, carrying out an exploratory factor analysis (EFA) and a confirmatory factor analysis (CFA). Result: The structure of the scale has been organized into three oblique factors. The findings confirmed the reliability and validity of the three dimensions of the EAS. Conclusion: Therefore, this scale is considered a valid option for assessing environmental action.